Pentingnya Perlindungan dan Keamanan Data Privasi di Era Digital - Abelia Mita Baqis; Muhammad Irwan Padli Nasution (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Along with the rapid development of the digital era, data privacy is now one of the most valuable assets for individuals and organisations. The increase in the use of information and communication technology also has the impact of increasing the potential for data breaches. Personal data, which includes information such as names, addresses, phone numbers, and financial data, is often a target for irresponsible parties. Data breaches can result in financial loss, reputation, and even threats to individual safety. Therefore, it is important to understand and implement effective protection measures to safeguard data privacy in this digital era. This paper reviews the urgency of personal data protection and security, the various challenges that arise, and the efforts that can be made to maintain the confidentiality of personal information. Using a qualitative approach, data is obtained from various literature sources and relevant case studies. The findings of this study indicate the need to raise awareness of the importance of safeguarding personal data, both at the individual and institutional levels, in order to prevent misuse of information. In addition, this research also suggests a number of strategies that can be implemented to strengthen the privacy data security system.